Membangun Body Image Melalui Acceptance and Commitment Therapy (ACT) pada Pasien Kanker Payudara - Ria Rizki Utami; Iswinarti Iswinarti; Djudiah Djudiah (Universitas Islam Indonesia, 2020)
Post-treatment for cancer patients have an impact on psychological discomfort, changes in lifestyle, fear and anxiety. One effect that often arises in breast cancer patients is a negative assessment of post-masectomy appearance such as breast removal. Development of body image problems related to low self acceptance in cancer patients. Interventions used to build a positive body image through acceptance and commitment therapy (ACT) in breast cancer patients. The design of study used a pretest-post-test control group design and the subjects involved in this study were breast cancer patients who were undergoing treatment at the age range of 30-50 years and had low score on body image scale. The data analysis method uses non-parametric analysis (Wilcoxon and Mann Whitney test) with SPSS. The results showed that ACT had an influence on body image in breast cancer patients. That is, ACT is able to build a positive body image in breast cancer patients